2011
DOI: 10.1002/mop.26146
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive‐fixed microbend long‐period fiber gratings with bandpass filter response

Abstract: improvements can then be made based on the full-wave simulation. The benefits of having an analytic effective-media reference that can be used for guiding retrieval are also worth noting. ABSTRACT: We demonstrate an adhesive-fixed periodic microbending whose transmission spectrum shows a bandpass filter response with the help of a fiber coil. In addition to thermal shift of the resonance wavelength, the transmission peak amplitude is varied with ambient temperature due to thermal expansion of the adhesive tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…[14b] The structure was simple but smart, and it was convenient for point or distributed sensing. [14b] Microbend sensor structure Stress Distributed and quasi-distributed system [54] Adhesive-fixed microbend sensor Bandpass filter All-fiber configuration and easy to build [55] Microbend long-period fiber gratings Twist angle Resonance wavelength shifts and splits when the optical fiber was twisted [56] Microbend sensor Stress Prediction of force based on ANN [57] The applications of microbend sensors in the biomedical fields are also very important due to their uses in key areas such as ballistocardiogram signal processing. [45] Such application in stress detection can also be extended to breath and heartbeat analysis.…”
Section: Applications In Stress Testing For Engineering and Biomedicinementioning
confidence: 99%
See 1 more Smart Citation
“…[14b] The structure was simple but smart, and it was convenient for point or distributed sensing. [14b] Microbend sensor structure Stress Distributed and quasi-distributed system [54] Adhesive-fixed microbend sensor Bandpass filter All-fiber configuration and easy to build [55] Microbend long-period fiber gratings Twist angle Resonance wavelength shifts and splits when the optical fiber was twisted [56] Microbend sensor Stress Prediction of force based on ANN [57] The applications of microbend sensors in the biomedical fields are also very important due to their uses in key areas such as ballistocardiogram signal processing. [45] Such application in stress detection can also be extended to breath and heartbeat analysis.…”
Section: Applications In Stress Testing For Engineering and Biomedicinementioning
confidence: 99%
“…The device had an all-fiber configuration and was easy to build. [55] Ivanov found that the resonance wavelength could show shifts and splits when the optical fiber was twisted, and the change in wavelength was related to the square of the twist angle. [56] This method was used to detect the twist angle with the microbend sensor, a principle that can be applied in the angle testing field and can be developed in future.…”
Section: Other Applicationsmentioning
confidence: 99%